Pelatihan Pembuatan Media Pembelajaran Bagi Guru MI NW Darussholohin Kalijaga dalam Rangka Meningkatkan Mutu Pembelajaran - Muhammad Innuddin; Hairani Hairani; Rifqi Hammad; Pahrul Irfan; Kurniadin Abd. Latif (LPPM Universitas Bumigora, 2021)
Technological developments that require teachers to improve skills in this field to help the teaching and learning process better. Teachers at Madrasah Ibtidaiyah Darussholihin NW Kalijaga are still lacking in applying technology, especially in making learning media. Based on these problems, it is necessary to hold training on how to use applications to develop learning media. Some applications that can be used as tools for creating learning media include the Microsoft PowerPoint application which is the most commonly used. This application is commonly used throughout the world to make presentation slides as a medium for delivering material in the teaching and learning process. The method used in this training activity is direct practice to develop learning media using Microsoft PowerPoint. With this service activity, it is hoped that all teachers can improve their abilities in developing learning media using the Microsoft PowerPoint application.